2016
DOI: 10.1177/0898264315624904
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Associations Between Perceived Measures of the Environment and Walking Among Brazilian Older Adults

Abstract: The perceived environment may affect walking for specific purposes among older adults. Investments in the environment may increase physical activity levels of older adults in Brazil.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
57
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(59 citation statements)
references
References 51 publications
1
57
0
1
Order By: Relevance
“…On the other hand, and considering the importance of paved surfaces for seniors walking activity [33], efforts aimed at guaranteeing certain levels of walking activity among seniors in urban and high walkable environments should be focusing on safety issues. This would be particularly relevant under rainy conditions, for instance, by investing in street design elements such as sidewalks or curb ramps, that are relevant in seniors' safety [39,44,45], and therefore contributing to reducing the risk of falling and the risk of accidents under such circumstances. Funding: The project leading to these results has received funding from "la Caixa" Foundation (ID 100010434).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, and considering the importance of paved surfaces for seniors walking activity [33], efforts aimed at guaranteeing certain levels of walking activity among seniors in urban and high walkable environments should be focusing on safety issues. This would be particularly relevant under rainy conditions, for instance, by investing in street design elements such as sidewalks or curb ramps, that are relevant in seniors' safety [39,44,45], and therefore contributing to reducing the risk of falling and the risk of accidents under such circumstances. Funding: The project leading to these results has received funding from "la Caixa" Foundation (ID 100010434).…”
Section: Discussionmentioning
confidence: 99%
“…These data can be explained in part by the fact that Florianópolis is a city potentially chosen for retirement. Thus, self-selection of places with greater leisure options, including physical activity resources, occurs 28 . Similar studies have shown that older adults choose to live in areas near public spaces as an environmental health promotion facilitator 11 .…”
Section: Discussionmentioning
confidence: 99%
“…Similar studies have shown that older adults choose to live in areas near public spaces as an environmental health promotion facilitator 11 . Data from a representative sample of older residents (n = 1,705) in Florianópolis reveal that the presence of parks and/or recreation facilities increases by 60% the chance of achieving ≥ 150 minutes/week of leisure-time physical activity 28 . This result is positive since the presence of public open spaces can contribute to increase and maintain of physical activity in this population 2 .…”
Section: Discussionmentioning
confidence: 99%
“…In our sample, living together with someone did not enhance the odds of outdoor independence. An explanation for this result may be that our measure did not reflect the extent to which one receives social support by the partner or family (Carlson et al 2012;Corseuil Giehl et al 2017); hence, specific types of social support may also facilitate outdoor independence.…”
Section: Discussionmentioning
confidence: 95%